1997
DOI: 10.1002/hep.510250323
|View full text |Cite
|
Sign up to set email alerts
|

Selective Loss of Binding Sites for the Glutamate Receptor Ligands [3H]Kainate and (S)–[3H]5–Fluorowillardiine in the Brains of Rats With Acute Liver Failure

Abstract: energy failure are currently considered to be There is increasing evidence that alterations of implicated. 1,2 glutamatergic function are implicated in the pathoGlutamate is the major excitatory neurotransmitter in the genesis of central nervous system consequences of mammalian central nervous system, where it activates ionoacute liver failure. The aim of the study was to assess tropic receptors (ligand-gated ion channels) and metabotropic the integrity of glutamate receptors in the brain in receptors (coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Similar results were obtained with experimental animals in chronic encephalopathy models (Baker et al 1990;Rossle et al 1990). Such animals at coma stages of encephalopathy showed unaltered [ 3 H]MK-801 binding to the NMDA receptor (similar to our findings), whereas a significant loss-up to 60%-of [ 3 H]kainate binding in hippocampus and cerebellum and of [ 3 H]5-fluorowillardiine binding to the AMPA receptor in hippocampus when compared to control animals were found (Michalak and Butterworth 1997). All these findings stand in sharp contrast to those in tautÀ/À mice in which [ 3 H]kainate binding was increased in parts of the hippocampus and in the cerebellum.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar results were obtained with experimental animals in chronic encephalopathy models (Baker et al 1990;Rossle et al 1990). Such animals at coma stages of encephalopathy showed unaltered [ 3 H]MK-801 binding to the NMDA receptor (similar to our findings), whereas a significant loss-up to 60%-of [ 3 H]kainate binding in hippocampus and cerebellum and of [ 3 H]5-fluorowillardiine binding to the AMPA receptor in hippocampus when compared to control animals were found (Michalak and Butterworth 1997). All these findings stand in sharp contrast to those in tautÀ/À mice in which [ 3 H]kainate binding was increased in parts of the hippocampus and in the cerebellum.…”
Section: Discussionsupporting
confidence: 77%
“…B bound, F free. Note that scaling for the two genotypes in a given region for a given receptor is always identical, but not for the different regions, nor for the different receptors correlation between brain taurine levels and [ 3 H]kainate binding, since we found that decreased taurine levels correlated with increased [ 3 H]kainate binding, and Michalak and Butterworth (1997) reported decreased [ 3 H]kainate binding if taurine levels were increased.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Such increases could result directly from diminished capacity for astrocytic uptake of glutamate as a consequence of decreased expression of GLT-1. Reduced expression of GLT-1 and the consequently increased extracellular brain glutamate concentrations also offers a possible explanation for the observed decrease in densities (down regulation) of AMPA/kainate binding sites also described in this model of acute liver failure [10]. Diminished uptake of neuronally released glutamate by the astrocyte as a consequence of decreased expression of GLT-1 would therefore constitute further evidence of impaired neuron-astrocytic trafficking of glutamate, a phenomenon which has previously been proposed to contribute to the pathogenesis of hepatic encephalopathy based on neurochemical studies [4]and by 13C-NMR spectroscopy [16]in portacaval-shunted rats.…”
mentioning
confidence: 51%
“…17,30,31 Based on these findings, it has been proposed that increased extracellular brain glutamate could be implicated in the pathogenesis of hepatic encephalopathy and brain edema in ALF. 32 In this same model of ALF, it has been proposed that increased extracellular glutamate concentrations in brain are the consequence of a loss in expression of the astrocytic glutamate transporter, GLT-1. 33 Furthermore, studies in cultured astrocytes suggest that the loss of glutamate transporter expression on astrocytes may be mediated by exposure to ammonia.…”
Section: Discussionmentioning
confidence: 99%